Delayed sigmoid colon perforation and enterocutaneous fistula due to tension free transvaginal tape operation for stress urinary incontinence - Lee, In Kyu; Sohn, Dong Wan (Canadian Urological Association Journal, 2015)
A 56-year-old female patient presented with sustained sigmoid colon perforation at the time of a tension-free vaginal tape (TVT) procedure and subsequently developed enterocutaneous fistula and subcutaneous abscess. She came to our emergency department complaining of left lower abdominal tenderness and swelling for 2 weeks previously. Her right thigh also was tender and swollen. A foreign body in sigmoid colon and subcutaneous abscess were found on computed tomography scan. We diagnosed the perforation of sigmoid colon and enterocutaneous fistula by TVT mesh. We performed laparoscopic excision of the mesh in sigmoid colon. We performed transobturator tape surgery for recurrence of stress urinary incontinence after 6 months.